Iranian Male and Female EFL Teachers' Attitudes towards Self-and Peer-Assessment in Descriptive Writing: A Mixed Methods Study - Hanyieh Davatgari Asl; Masoud Zoghi; Peiman Rahmani (International Journal of Instructional Technology and Educational Studies)
AbstractThe main purpose of this exploratory sequential mixed methods study was to elicit Iranian male and female EFL teachers’ attitudes towards self-and peer-assessment in descriptive writing. To reach the research goals of the study, a questionnaire based on Bartlett (2015) and Spencer (2005) models was developed in two various strands. In the qualitative strand, six themes were taken from the administered interviews to predict Iranian male and female EFL teachers' attitudes namely: "cooperation and positivity", "independence", "practice", " strengths and weaknesses". In the quantitative strand, exploratory factor analysis (EFA) was used to validate the recommended themes and to test the participants' attitudes one way-MANOVA was manifested, too. The whole results of the two strands represented the fact that Iranian male and female EFL teachers had positive attitudes towards self-and peer-assessment in descriptive writing, and there was a statistical significant difference between males and females. Additionally, the findings of the research indicated that Bartlett (2015) and Spencer (2005) models were useful in increasing the research participants' knowledge in descriptive writing. Ultimately, these can have implications especially with regard to assessment issues not only EFL language teachers but also for EFL language learners.